A modern tool for a modern student. Video games in the exploration and learning of mathematics - Solarz, Izabela (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
Solving equations is one of the central topics in mathematics curricula. Teachers would like to pay more attention to building formulas and formulating algebraic models because modern students dare to translate a problem situation into algebra, but very often their students are helpless because of the lack of practice. There is not much time for exercises. The problem is how to help students with acquiring algebraic skills, like transforming expressions and solving equations. There is a new medium in education that can be used for this – video games. Could they help? I designed a special learning arrangement using a special game that was built for learning algebra. The results suggest that This can be a really relevant didactic medium for teaching mathematics
Didactics of Mathematics, 2014, Nr 11 (15), s. 65-74
Keywords: algebraic skills; unintentional learning; game